PERBANDINGAN PENGGUNAAN DAYA LISTRIK MOTOR INDUKSI SEBAGAI PENGGERAK KOMPRESOR PADA SIANG HARI DAN MALAM HARI PADA INDUSTRI ES BALOK - Liem Ek Bien, Liem Ek Bien; Peter, Peter (Jurnal Teknik Elektro, 2005)
In ice block industry, usage of electrical power for induction motor as prime mover ofcompressor is very high. Level of usage of electricity at ice block industry base on change ofrefrigeration media temperature. Referring to the mentioned, hence mass flow rate ofrefrigerant circulating in system, refrigeration effect per kilogram, comparison ofcompression of compressor, refrigeration capacities and mechanic energy which must beyielded by the compressor to circulate the refrigerant determining transfer of heat systemperformance as work principle of cooler machine can be determined. This Final Assignmentpresent an economical technique of usage of electrical power of induction motor that is byproduct the ice block when of media refrigeration temperature reach the lowest level that isnight time with method comparison of usage of electrical power of induction motor as primemover of compressor at ice block industry which giving result the lowest usage of electricalpower. Case study done at ice block factory that is PT. KARAHARJA TIRTATAMA.Key words: Induction Motor, Refrigeneration Temperature, Electrical Power